Composite heat insulation film prepared based on high-transparency room-temperature phase change material and method thereof
Patent Information
- Application Number
- CN202310795142.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-06-30
AI Technical Summary
这些方法对于二氧化钒薄膜的热致变色性能有一定提升,但Mo5+、W6+等高价金属元素的掺杂会导致VO2材料的光学性能低以及热滞回线宽化等问题,同时折射率低的SiO2、TiO2等外壳层等的引入也会使得VO2材料出现相变滞后现象
1.通过引入壳层SiO2增加VO2可见光透过率及VO2粉体的分散性,并通过介孔的结构解决由于外壳层包覆VO2引起的相变滞后现象。
Smart Images

Figure CN116970193B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional materials / smart window technology, and in particular to a method for preparing composite heat-insulating films based on highly transparent room temperature phase change materials. Background Technology
[0002] M-phase VO2 undergoes a reversible phase transition at 68℃. Below the phase transition temperature, VO2 exists in a monoclinic semiconductor state (M-phase), allowing most near-infrared light to pass through. Above the phase transition temperature, VO2 exists in a rutile tetragonal metallic state (R-phase), reflecting and absorbing near-infrared light, thus providing heat insulation. Furthermore, it maintains constant transmittance in the visible light range during the phase transition, making VO2 an ideal material for smart windows.
[0003] Although VO2 possesses excellent phase transition properties, its high phase transition temperature (compared to room temperature), poor optical performance, and poor weather resistance limit the practical application of vanadium dioxide thin films. To address these issues, researchers have employed various methods, such as elemental doping, core-shell structures, and multilayer film design. These methods have improved the thermochromic properties of vanadium dioxide thin films to some extent, but Mo... 5+ W 6+ The doping of high-valence metal elements can lead to problems such as low optical performance and broadened thermal hysteresis loops in VO2 materials. Furthermore, the introduction of shell layers with low refractive indices, such as SiO2 and TiO2, can cause phase transition hysteresis in VO2 materials. Moreover, the fabrication of multilayer thin films is often a complex process with high requirements for instruments, operation, and environment.
[0004] Therefore, there is a need for a method to prepare a highly transparent vanadium dioxide composite film that can undergo a reversible phase transition at room temperature and has both high optical performance and excellent thermal insulation performance. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention aims to provide a method for preparing highly transparent room-temperature phase change materials and their application in composite thermal insulation films. It utilizes a SiO2 shell to increase the visible light transmittance of VO2 and the dispersibility of VO2 powder, and solves the phase change hysteresis caused by the outer shell encapsulating VO2 through a mesoporous structure. The core-shell structured nanoparticles possess a wide controllable range of phase change temperatures, small mesopore size, and thin shell thickness; the polymer composite film exhibits high visible light transmittance and thermal insulation performance, as well as strong acid resistance and oxidation resistance.
[0006] The present invention is achieved through the following technical solution.
[0007] According to one aspect of the present invention, a method for preparing a composite thermal insulation film based on a highly transparent room temperature phase change material is provided, comprising the following steps: 1) In an alcohol-water mixture, X-doped modified M-phase VO2 nanomaterials were blended with organosilicon and a mesoporous reagent, and the mixture was heated and stirred to obtain the desired product. n V 1-n O 2-m Y m (M) Core-shell structured powder material with in-situ grown silica shell on surface X n V 1-n O 2-m Y m (M)@SiO2; X is Mo or W, Y is F; 2) Removal of X by solvent reflux extraction n V 1-n O 2-m Y m A mesoporous template on the (M)@SiO2 surface was used to obtain highly transparent mesoporous silicon encapsulated with X, exhibiting efficient anti-reflection and anti-reflection properties for visible light. n V 1-n O 2-m Y m (M) Powder Material X n V 1-n O 2-m Y m (M)@SiO2; 3) X n V 1-n O 2-m Y m (M)@m-SiO2 powder was dispersed in a polymer solution at a mass ratio of (0.5-10):(90-99.5) to obtain a homogeneous casting solution. The casting solution was then deposited onto a glass substrate using a spraying or scraping method, followed by low-temperature drying and curing to obtain a highly transparent room-temperature phase change composite material X. n V 1-n O 2-m Y m (M)@m-SiO2 polymer composite thermal insulation film.
[0008] According to an exemplary embodiment of the present invention, n takes the value of 0.01 to 0.04, and m takes the value of 0.01 to 0.04; or n=0, m=0, and undoped pure M-phase VO2.
[0009] According to an exemplary embodiment of the present invention, organosilicon includes silane oxides or polysiloxanes; The silane oxide is tetraethyl orthosilicate, methyl orthosilicate, or methyltrimethylethoxysilane; The polysiloxane is poly(diethoxysiloxane) or poly(dimethylsiloxane).
[0010] According to an exemplary embodiment of the present invention, the mesoporous template agent includes a cationic surfactant or a nonionic surfactant; The cationic surfactant is hexadecyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium bromide (DTAB), octadecyltrimethylammonium bromide (STAB), or tetramethylammonium bromide (TMABr). The nonionic surfactant is polyethylene glycol (PEG) or poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock polymer P123.
[0011] According to an exemplary embodiment of the present invention, the reflux extraction solvent is hydrochloric acid-ethanol, ethanol or acetone, the reflux time is 4-10 h, and the reflux temperature is 75-90 °C.
[0012] According to an exemplary embodiment of the present invention, the polymer of the polymer solution includes PVC, PVDF, PVB, PVP, PMMA or Ps with a molecular weight between 100,000 and 600,000.
[0013] According to an exemplary embodiment of the present invention, the solvent of the polymer solution includes water, ethanol, tetrahydrofuran, or acetone.
[0014] According to another aspect of the present invention, a composite thermal insulation film is prepared based on a highly transparent room temperature phase change material.
[0015] The present invention, by adopting the above technical solution, has the following beneficial effects: 1. By introducing a shell layer of SiO2, the visible light transmittance of VO2 and the dispersibility of VO2 powder are increased, and the phase transition hysteresis caused by the shell layer coating of VO2 is solved by the mesoporous structure.
[0016] 2. X-rays with adjustable phase transition temperatures of 38-68℃, adjustable mesopore diameters of 2-15nm, and adjustable silicon shell thickness of 10-60nm were prepared. n V 1-n O 2-m Y m (M)@m-SiO2 core-shell structured nanoparticles improve the visible light transmittance of vanadium dioxide thermochromic films by adjusting the pore size and layer thickness. This significantly improves the visible light transmittance of VO2 films while maintaining the good infrared heat insulation performance of traditional M-phase VO2 thermochromic films.
[0017] 3. Due to the low interfacial energy effect of the mesoporous silica coating, it provides good blendability with polymers. The presence of low interfacial energy in the mesoporous silica makes X... n V 1-n O 2-m Y m(M)@m-SiO2 maintains good dispersibility in polymer solutions, and VO2 powder can be uniformly dispersed in polymer solutions. While increasing visible light transmittance, it also ensures certain heat insulation performance, making it possible to form films by spraying or scraping.
[0018] X n V 1-n O 2-m Y m The visible light transmittance of the (M)@m-SiO2 polymer composite film is 45%-82.2%, and the film's thermal insulation performance is good. At T=5-25℃, the acid resistance of the powder in 0.5 M H2SO4 solution is 30 min-5 d, and the antioxidant performance in 0.1 M H2O2 solution is 10 min-12 h.
[0019] Compared with traditional magnetron sputtering or vapor deposition methods for preparing VO2 thin films, the present invention significantly reduces the film production cost and facilitates large-scale industrial production of VO2 thin films of various thicknesses to meet different needs. This preparation method has the advantages of simple equipment, easy control, low production cost, and ease of factory production. Attached Figure Description
[0020] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, do not constitute an undue limitation of the invention. In the drawings: Figure 1 X-ray diffraction (XRD) pattern of the core-shell structured VO2(M)@m-SiO2 nanoparticles prepared in Example 1; Figure 2 X-ray diffraction (XRD) pattern of the core-shell structured VO2(M)@m-SiO2 nanoparticles prepared in Example 2; Figure 3 High-resolution transmission electron microscopy (HRTEM) image of the core-shell structured VO2(M)@m-SiO2 nanoparticles prepared in Example 1; Figure 4 High-resolution transmission electron microscopy (HRTEM) image of the core-shell structured VO2(M)@m-SiO2 nanoparticles prepared in Example 2; Figure 5 Nitrogen adsorption-desorption curves and pore size step-by-step diagrams of the core-shell structured VO2@m-SiO2 nanoparticles prepared in Example 3; Figure 6 The UV-Vis transmittance of the VO2@m-SiO2 polymer composite films prepared in Examples 1, 2, and 3 is shown in the diagram. Figure 7 The thermal insulation performance diagram of the VO2@m-SiO2 polymer composite film prepared in Example 3 is shown. Figure 8 Mo prepared in Example 4 0.02 V 1.98 UV-Vis transmittance of O2@m-SiO2 polymer composite film; Figure 9 Mo prepared in Example 4 0.02 V 1.98 Thermal insulation performance diagram of O2@m-SiO2 polymer composite film. Detailed Implementation
[0021] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention.
[0022] This invention provides a method for preparing a highly transparent room-temperature phase change material, comprising the following steps: Step 1: Prepare element-doped modified M-phase VO2 powder material coated with SiO2 using the sol-gel method. In an alcohol-water mixture with an alcohol-water ratio of 4:1 to 8:1, M-phase VO2 nanomaterials (X-doped with element X, exhibiting temperature-induced phase transition characteristics) were added. n V 1-n O 2-m Y m (M) is blended with organosilicon and mesoporous template agent, X n V 1-n O 2-m Y m The mass ratio of (M), organosilicon, mesoporous template agent, and alcohol / water mixture was 0.1:(0.05-0.2):(0.07-0.21):58. The reaction was carried out under water bath heating and stirring at 25-35℃ to obtain the product in X. n V 1-n O 2-m Y m (M) Core-shell structured powder material with in-situ grown silica shell on surface (X) n V 1-n O 2-m Y m (M)@SiO2).
[0023] The general formula of X-doped and modified M-phase VO2 nanomaterials is X. n V 1-n O 2-m Y m (M) (n / m < 1), where X is Mo or W, Y is F; n or m is the ratio of the amount of substance of element X or Y to element V, n takes a value of 0.01 to 0.04, and m takes a value of 0.01 to 0.04.
[0024] In one embodiment, n=0, m=0, representing undoped pure M-phase VO2.
[0025] The aforementioned organosilicones include silane oxides or polysiloxanes; The silane oxides are tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), or methyltrimethylethoxysilane (ETMS); the polysiloxanes are polydiethoxysiloxane (PDEOS) or polydimethylsiloxane (PDES).
[0026] The aforementioned mesoporous template agents include cationic surfactants or nonionic surfactants; The cationic surfactants are hexadecyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium bromide (DTAB), octadecyltrimethylammonium bromide (STAB), or tetramethylammonium bromide (TMABr).
[0027] The nonionic surfactant is polyethylene glycol (PEG) or poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock polymer P123.
[0028] Step 2: Remove X by solvent reflux extraction. n V 1-n O 2-m Y m A mesoporous template on the (M)@SiO2 surface was used to obtain highly transparent mesoporous silicon encapsulated with X, exhibiting efficient anti-reflection and anti-reflection properties for visible light. n V 1-n O 2-m Y m (M) Powder materials (X) n V 1-n O 2-m Y m (M)@SiO2).
[0029] The reflux extraction solvent is a polar solvent such as hydrochloric acid-ethanol, ethanol, or acetone. The reflux time is 4-10 h, and the reflux temperature is 75-90 °C, adjusted according to the choice of mesoporous template agent. The mesoporous template is removed by reflux extraction to obtain X. n V 1-n O2(M)@m-SiO2 modified powder.
[0030] Step 3, X n V 1-n O 2-m Y m(M)@m-SiO2 powder was dispersed in a polymer solution with a mass ratio of (0.5-10):(90-99.5) at a concentration of 5-20 wt% to obtain a homogeneous casting solution. The casting solution was then deposited onto a glass substrate using spraying or blade coating methods. The blade coating thickness was 50µm-150µm. The spraying range was 2cm×2cm-10cm×10cm, with a feed rate of 0.1-0.3mL / min, a spraying step size of 2mm, a spraying height of 40mm, a feed rate of 600mm / min, and a rapid traverse speed of 1000mm / min. The film was dried and cured at 30℃ to obtain X-rays with high transparency and temperature-induced phase change properties. n V 1-n O 2-m Y m (M)@m-SiO2 polymer composite thermal insulation film.
[0031] The polymer solution contains polymers, including but not limited to PVC, PVDF, PVB, PVP, PMMA or Ps with good transparency properties, and molecular weights between 100,000 and 600,000.
[0032] The solvent includes, but is not limited to, one or a mixture of two or three low-boiling-point volatile solvents such as water, ethanol, tetrahydrofuran, and acetone, and the solvent is adjusted accordingly based on the choice of polymer.
[0033] The prepared core-shell structure X n V 1-n O 2-m Y m The phase transition temperature of (M)@m-SiO2 nanopowder is 40-68℃; the mesopore size is 2-10nm; and the silicon shell thickness is 10-60nm.
[0034] Prepared X n V 1-n O 2-m Y m The visible light transmittance of (M)@m-SiO2 polymer composite films ranges from 45% to 82.2%, which is about 5-15% higher than that of typical heat-insulating film materials with VO2 doping levels between 5-70 wt%. (Film heat insulation performance) Between T=5-25℃, the acid resistance of the powder in 0.5 M H2SO4 solution is 30 min-5 d, and the antioxidant performance in 0.1 M H2O2 solution is 10 min-12 h.
[0035] The present invention will be further illustrated below through different embodiments.
[0036] Example 1 1) Take VO2(M)(X) n V 1-n O2-m Y m (M), n = 0, m = 0, undoped / modified M-phase VO2) according to X n V 1-n O 2-m Y m (M), organosilicon reagent methyltrimethylethoxysilane (ETMS), mesoporous template agent octadecyltrimethylammonium bromide STAB, and alcohol / water mixed solvent in a mass ratio of 0.1:0.11:0.10:58, weigh VO2(M)T C At 67℃, ETMS and STAB were dispersed in a 4:1 alcohol-water mixture and stirred at 35℃ for 12 hours. The mixture was then filtered and washed three times with anhydrous ethanol and deionized water, respectively.
[0037] 2) The collected precipitate was refluxed in acetone solution at 80°C for 6 hours, filtered, washed three times with anhydrous ethanol and deionized water respectively, and dried at 60°C for 24 hours to obtain VO2(M)@m-SiO2 nanoparticles.
[0038] 3) X n V 1-n O 2-m Y m (M)@m-SiO2 powder was dispersed in a 12% PMMA acetone solution at a mass ratio of 0.5:99.5 and stirred thoroughly for 12 hours to obtain a casting solution. The solution was then coated onto a glass substrate using 50, 75, 100, and 150µm doctor blades.
[0039] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the core-shell structured VO2(M)@m-SiO2 nanoparticles prepared in Example 1. Figure 3 High-resolution transmission electron microscopy (HRTEM) images of the core-shell structured VO2(M)@m-SiO2 nanoparticles prepared in Example 1 are shown. The images reveal diffraction peaks at 26.9°, 27.8°, 36.9°, 42.3°, 55.5°, and 56.9°, corresponding to the (-1 1 1), (0 1 1), (-2 0 2), (2 1 0), (-2 2 2), and (-1 1 3) crystal planes, respectively, which correspond to the standard card for monoclinic VO2 (JCPDS No. 09-0142), and the peaks are sharp. This indicates that the mesoporous silica-coated VO2 core-shell composite powder prepared by this method does not alter the crystal phase of the core VO2(M). The 0.32 nm lattice spacing in the core corresponds to the (011) plane of the monoclinic VO2, and the outer silicon shell is approximately 40 nm thick.
[0040] Example 2 1) Take VO2(M)(X) n V 1-n O2-m Y m (M), n = 0, m = 0, undoped / modified M-phase VO2) according to X n V 1-n O 2-m Y m The mass ratio of (M) to the organic silicon reagent methyl orthosilicate (TMOS), the mesoporous template agent dodecyltrimethylammonium bromide (DTAB), and the alcohol / water mixed solvent is 0.1:0.09:0.07:58. Weigh out VO2(M)T C TMOS and STAB were dispersed in an alcohol-water mixture with a 5:1 ratio at 67℃ and stirred at 25℃ for 12 hours. The mixture was then filtered and washed three times with anhydrous ethanol and deionized water, respectively.
[0041] 2) The collected precipitate was refluxed in ethanol solution at 75°C for 10 h, filtered, washed three times with anhydrous ethanol and deionized water respectively, and dried at 60°C for 24 h to obtain VO2(M)@m-SiO2 nanoparticles.
[0042] 3) X n V 1-n O 2-m Y m (M)@m-SiO2 powder was dispersed in a 10wt% PVP aqueous solution at a mass ratio of 2:98 and stirred thoroughly for 10 h to obtain a casting solution. The solution was then coated onto a glass substrate using 50, 75, 100, and 150µm doctor blades.
[0043] Figure 2 The X-ray diffraction (XRD) pattern of the core-shell structured VO2(M)@m-SiO2 nanoparticles prepared in Example 2 is shown below. Figure 4 The high-resolution transmission electron microscope (HRTEM) image of the core-shell structured VO2(M)@m-SiO2 nanoparticles prepared in Example 2 shows that the diffraction peaks at 26.9°, 27.8°, 36.9°, 42.3°, 55.5°, and 56.9° correspond to the (-1 1 1), (0 1 1), (-2 0 2), (2 1 0), (-2 2 2), and (-1 1 3) crystal planes, respectively, which are consistent with the standard card for monoclinic VO2 (JCPDS No. 09-0142). The peaks are sharp, and the core remains VO2(M). The 0.32 nm lattice spacing in the core corresponds to the (011) plane of the monoclinic VO2, and the outer silicon shell is approximately 15 nm thick.
[0044] Example 3 1) Take VO2(M)(X) n V 1-n O 2-m Y m(M), n = 0, m = 0, undoped / modified M-phase VO2) according to X n V 1-n O 2-m Y m (M), organosilicon reagent tetraethyl orthosilicate (TEOS); mesoporous template agent hexadecyltrimethylammonium bromide (CTAB); alcohol / water mixed solvent in a mass ratio of 0.1:0.16:0.07:58, weigh out VO2(M)T C TEOS and CTAB were dispersed in an alcohol-water mixture with an alcohol-to-water ratio of 8:1 at 67℃ and stirred at 30℃ for 12 hours. The mixture was then filtered and washed three times with anhydrous ethanol and deionized water, respectively.
[0045] 2) The collected precipitate was refluxed in acetone solution at 85°C for 4 hours, filtered, washed three times with anhydrous ethanol and deionized water respectively, and dried at 60°C for 24 hours to obtain VO2(M)@m-SiO2 nanoparticles.
[0046] 3) X n V 1-n O 2-m Y m (M)@m-SiO2 powder was dispersed in a 5wt% PVB ethanol solution at a mass ratio of 5:95 and stirred thoroughly for 6 hours to obtain a casting solution. The solution was then coated onto a glass substrate using 50, 75, 100, and 150µm doctor blades.
[0047] Figure 5 The nitrogen adsorption-desorption curves and pore size step-by-step diagrams of the core-shell structured VO2@m-SiO2 nanoparticles prepared in Example 3 are shown. Figure 7 The figure shows the thermal insulation performance of the VO2@m-SiO2 polymer composite film prepared in Example 3. As can be seen from the figure, the silica shell exhibits a mesoporous structure, and the nitrogen adsorption-desorption curve shows a typical type IV curve, indicating the presence of small mesopores of approximately 4 nm. The thermal insulation performance of the films prepared at blade thicknesses of 50, 75, 100, and 150 µm is also shown. T=4-8℃.
[0048] Figure 6The figures show the UV-Vis transmittance of the VO2@m-SiO2 polymer composite films prepared in Examples 1, 2, and 3. As can be seen from the figures, the visible light transmittance of the composite film in Example 1 at thicknesses of 50, 75, 100, and 150 µm is 61.4%, 57.3%, 55.1%, and 49.4%, respectively; the visible light transmittance of the composite film in Example 2 at thicknesses of 50, 75, 100, and 150 µm is 61.8%, 51.2%, 50.4%, and 46.8%, respectively; and the visible light transmittance of the composite film in Example 3 at thicknesses of 50, 75, 100, and 150 µm is 66.4%, 62.6%, 57.2%, and 49.8%, respectively.
[0049] Example 4 1) Take Mo 0.02 V 1.98 O2(M)(X) n V 1-n O 2-m Y m (M), n = 0.02, m = 0) according to X n V 1-n O 2-m Y m (M), organosilicon reagent poly(diethoxysiloxane) (PDEOS), mesoporous template agent tetramethylammonium bromide (TMABr), and alcohol / water mixed solvent in a mass ratio of 0.1:0.16:0.07:58, weigh Mo 0.02 V 1.98 O2(M)T C TEOS and CTAB were dispersed in a 6:1 alcohol-water mixture at 48℃ and stirred at 35℃ for 12 hours. The mixture was then filtered and washed three times with anhydrous ethanol and deionized water, respectively.
[0050] 2) The collected precipitate was refluxed in acetone solution at 80°C for 6 hours, filtered, washed three times each with anhydrous ethanol and deionized water, and dried at 60°C for 24 hours to obtain Mo. 0.02 V 1.98 O2(M)@m-SiO2 nanopowder.
[0051] 3) X n V 1-n O 2-m Y m (M)@m-SiO2 powder was dispersed in a 20wt% PVB ethanol solution at a mass ratio of 7:93 and stirred thoroughly for 6 hours to obtain a casting solution. The solution was then coated onto a glass substrate using a scraper.
[0052] Figure 8 Mo prepared in Example 4 0.02 V 1.98UV-Vis transmittance of O2@m-SiO2 polymer composite film; Figure 9 Mo prepared in Example 4 0.02 V 1.98 The graph shows the thermal insulation performance of the O2@m-SiO2 polymer composite film. As can be seen from the graph, the visible light transmittance of the composite film at thicknesses of 50, 75, 100, and 150 µm is 70.3%, 59.3%, 58.1%, and 53.3%, respectively. The thermal insulation performance is... T=6-13℃.
[0053] Example 5 1) Take Mo 0.02 V 1.98 O 1.97 F 0.03 (M)(X) n V 1-n O 2-m Y m (M), n = 0.02, m = 0.03) according to X n V 1-n O 2-m Y m (M), organosilicon reagent polydimethylsiloxane (PDES), mesoporous template agent polyethylene glycol (PEG), and alcohol / water mixed solvent in a mass ratio of 0.1:0.05:0.12:58, weigh Mo 0.02 V 1.98 O 1.97 F 0.03 (M)T C TEOS and P123 were dispersed in an alcohol-water mixture with a 7:1 alcohol-water ratio at 38℃ and stirred at 30℃ for 12 hours. The mixture was then filtered and washed three times with anhydrous ethanol and deionized water, respectively.
[0054] 2) The collected precipitate was refluxed in ethanol solution at 80°C for 10 h, filtered, washed three times each with anhydrous ethanol and deionized water, and dried at 60°C for 24 h to obtain Mo. 0.02 V 1.98 O 1.97 F 0.03 (M)@m-SiO2 nanopowder.
[0055] 3) X n V 1-n O 2-m Y m (M)@m-SiO2 powder was dispersed in a 18wt% Ps tetrahydrofuran solution at a mass ratio of 10:90 and stirred thoroughly for 6 hours to obtain a casting solution. The solution was then coated onto a glass substrate using a scraper.
[0056] Example 6 1) Take Mo0.01 V 1.99 O 1.97 F 0.03 (M)(X) n V 1-n O 2-m Y m (M), n = 0.01, m = 0.03) according to X n V 1-n O 2-m Y m (M), organosilicon reagent tetraethyl orthosilicate (TMOS), mesoporous template agent poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock polymer P123, and alcohol / water mixed solvent in a mass ratio of 0.1:0.2:0.21:58, weigh Mo 0.01 V 1.99 O 1.97 F 0.03 (M)T C TEOS and P123 were dispersed in an alcohol-water mixture with a 4:1 ratio at 46℃ and stirred at 35℃ for 12 hours. The mixture was then filtered and washed three times with anhydrous ethanol and deionized water, respectively.
[0057] 2) The collected precipitate was refluxed in hydrochloric acid-ethanol solution at 90°C for 4 hours, filtered, washed three times each with anhydrous ethanol and deionized water, and dried at 60°C for 24 hours to obtain Mo. 0.01 V 1.99 O 1.97 F 0.03 (M)@m-SiO2 nanopowder.
[0058] 3) X n V 1-n O 2-m Y m (M)@m-SiO2 powder was dispersed in a 15wt% PVP ethanol solution at a mass ratio of (0.5-10):(90-99.5) and stirred thoroughly for 10 h to obtain a casting solution. The solution was then applied to a glass substrate using a spray coating machine. The spraying area was 8cm × 8cm, the feed rate was 0.1mL / min, the spraying step size was 2mm, the spraying height was 40mm, the feed rate was 600mm / min, and the rapid traverse speed was 1000mm / min.
[0059] The following comparative examples are given in comparison with the embodiments of the present invention to further illustrate the effects of the present invention.
[0060] The specific preparation process of the comparative example: 1) Take VO2(M)(X) n V 1-n O 2-m Y m(M), n = 0, m = 0, undoped / modified M-phase VO2) according to X n V 1-n O 2-m Y m The mass ratio of (M), organosilicon reagent, and alcohol / water mixed solvent is 0.1:0.16:58. Weigh out VO2(M)T. C TEOS was dispersed in a 4:1 alcohol-water mixture at 66℃ and stirred at 30℃ for 12 h. The mixture was then filtered and washed three times with anhydrous ethanol and deionized water, respectively. Finally, it was dried at 60℃ for 24 h to obtain VO2(M)@SiO2 nanoparticles.
[0061] 2) Weigh 0.05g of VO2(M)@SiO2 nanoparticles and disperse them in 5% PVB ethanol solution. Stir thoroughly for 12h to obtain casting solution. Coat the film on a glass substrate using a 150µm doctor blade.
[0062] 3) The visible light transmittance of the fabricated membrane at a thickness of 150µm was 44.8%.
[0063] The comparative example is non-mesoporous VO2(M)@SiO2, and the specific data are shown in Table 1. Table 1. Comparison of phase transition temperature, visible light transmittance, and thermal insulation performance between the present invention and comparative examples.
[0064] As shown in Table 1, the high-transparency mesoporous silicon (m-SiO2)-coated room-temperature phase-change M-phase VO2 material and its composite thermal insulation film proposed in this invention exhibit significantly improved visible light performance and relatively higher thermal insulation properties compared to the non-mesoporous VO2(M)@SiO2 composite film in Example 1. Furthermore, after doping with certain elements, it achieves a phase transition temperature close to room temperature. This demonstrates that the X prepared in this invention... n V 1-n O 2-m Y m (M) composite film can provide a certain degree of heat insulation while ensuring high visible light transmittance.
[0065] This invention prepares a room-temperature phase change polymer composite film material with high transparency, exhibiting a visible light transmittance of 45%-82.2%. It demonstrates acid resistance in 0.5 M H₂SO₄ solution for 30 min-5 days, antioxidant performance in 0.1 M H₂O₂ solution for 10 min-12 h, and good thermal insulation properties. The temperature (T) can reach 5-25℃. The X-ray material prepared in this invention exhibits temperature-induced phase transition properties. n V 1-n O 2-m Y m(M)@m-SiO2 polymer composite thermal insulation film not only has high visible light transmittance, but also has excellent thermal insulation ability and certain weather resistance.
[0066] This invention is not limited to the above embodiments. Based on the technical solutions disclosed in this invention, those skilled in the art can make some substitutions and modifications to some of the technical features without creative effort, and all such substitutions and modifications are within the protection scope of this invention.
Claims
1. A method for preparing a composite thermal insulation film based on a highly transparent room-temperature phase change material, characterized in that, Includes the following steps: 1) In an alcohol-water mixture, X-doped modified M-phase VO2 nanomaterials or undoped pure M-phase VO2 nanomaterials are blended with organosilicon and a mesoporous reagent, and the mixture is heated and stirred to obtain the desired product. n V 1-n O 2-m Y m (M) Core-shell structured powder material with in-situ grown silica shell on surface X n V 1-n O 2-m Y m (M)@SiO2; X is Mo or W, Y is F; n takes values from 0.01 to 0.04, m takes values from 0.01 to 0.04; or n=0, m=0; 2) Removal of X by solvent reflux extraction n V 1-n O 2-m Y m A mesoporous template on the (M)@SiO2 surface was used to obtain a mesoporous silicon encapsulated with X material that exhibits high transparency to visible light. n V 1-n O 2-m Y m (M) Powder Material X n V 1-n O 2-m Y m (M)@m-SiO2; 3) X n V 1-n O 2-m Y m (M)@m-SiO2 powder was dispersed in a polymer solution at a mass ratio of (0.5-10):(90-99.5) to obtain a homogeneous casting solution. The casting solution was then deposited onto a glass substrate using a spraying or scraping method, followed by low-temperature drying and curing to obtain a highly transparent room-temperature phase change composite material X. n V 1-n O 2-m Y m (M)@m-SiO2 polymer composite thermal insulation film.
2. The method for preparing a composite thermal insulation film based on a highly transparent room-temperature phase change material according to claim 1, characterized in that, Organosilicones include silane oxides or polysiloxanes; The silane oxide is tetraethyl orthosilicate, methyl orthosilicate, or trimethylethoxysilane. The polysiloxane is poly(diethoxysiloxane) or poly(dimethylsiloxane).
3. The method for preparing a composite heat-insulating film based on a highly transparent room-temperature phase change material according to claim 1, characterized in that, Mesoporous template agents include cationic surfactants or nonionic surfactants; The cationic surfactant is hexadecyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium bromide (DTAB), octadecyltrimethylammonium bromide (STAB), or tetramethylammonium bromide (TMABr). The nonionic surfactant is polyethylene glycol (PEG) or poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock polymer P123.
4. The method for preparing a composite thermal insulation film based on a highly transparent room-temperature phase change material according to claim 1, characterized in that, The reflux extraction solvent is hydrochloric acid-ethanol, ethanol, or acetone, the reflux time is 4-10 h, and the reflux temperature is 75-90℃.
5. The method for preparing a composite thermal insulation film based on a highly transparent room-temperature phase change material according to claim 1, characterized in that, The polymers in the polymer solution include PVC, PVDF, PVB, PVP, PMMA, or Ps with molecular weights between 100,000 and 600,000.
6. The method for preparing a composite thermal insulation film based on a highly transparent room-temperature phase change material according to claim 1, characterized in that, Solvents for polymer solutions include water, ethanol, tetrahydrofuran, or acetone.
7. A composite thermal insulation film prepared by the method of any one of claims 1-6 based on a highly transparent room temperature phase change material.
8. The composite thermal insulation film prepared based on a highly transparent room-temperature phase change material according to claim 7, characterized in that, Precursor materials for composite thermal insulation films: core-shell structure X n V 1-n O 2-m Y m The phase transition temperature of (M)@m-SiO2 nanopowder is 40-68℃; the mesopore size is 2-10nm; and the silicon shell thickness is 10-60nm.
9. The composite thermal insulation film prepared based on a highly transparent room temperature phase change material according to claim 7, characterized in that, X n V 1-n O 2-m Y m The visible light transmittance of the (M)@m-SiO2 polymer composite film is 45%-82.2%, and the film's thermal insulation performance is good. At T=5-25℃, the acid resistance of the powder in 0.5 M H2SO4 solution is 30 min-5 d, and the antioxidant performance in 0.1 M H2O2 solution is 10 min-12 h.
Citation Information
Patent Citations
Method for preparing silica-coated vanadium dioxide nanoparticles through alcohol-water solution method
CN105858725A
Intelligent heat-insulating composite coating with high visible light transmittance and preparation method of intelligent heat-insulating composite coating
CN113105765A